The high recycling folded cascode (HRFC): A general enhancement of the recycling folded cascode operational amplifier. (July 2019) - Yosefi, Ghader
Abstract: In this paper, an enhanced CMOS recycling folded cascode (RFC) operational amplifier (Op-Amp) is presented. It is based on the high recycling folded cascode (HRFC) in amplifying the transconductance at the output by shorting two nodes in the RFC structure. Compared to the conventional RFC, our circuit is capable to enhance DC gain and unity gain bandwidth (UGBW) in the same power consumption. Moreover, the improvements of the proposed circuit are in better input-referred noise, fast-settling time, input-offset voltage, total harmonic distortion (THD), common mode rejection ratio (CMRR) and power supply rejection ratio (PSRR). Simulation results in 180 nm CMOS standard technology confirm the theoretical results and indicate that our circuit has a good figure of merit (FoM). Compared to the RFC, the proposed HRFC has 1.8 times the UGBW (247 versus 137 MHz) and also has 6 times gain boosting (73 versus 57 dB) in the same power supply (1.8 V), power consumption and driving capacitor load of 5 pF.